Association of serum potassium concentration with mortality and ventricular arrhythmias in patients with acute myocardial infarction: A systematic review and meta-analysis. (April 2018) - Colombo, Miriam Giovanna; Kirchberger, Inge; Amann, Ute; Dinser, Lisa; Meisinger, Christa
Background: Challenging clinical practice guidelines that recommend serum potassium concentration between 4.0–5.0 mEq/L or ≥4.5 mEq/L in patients with acute myocardial infarction, recent studies found increased mortality risks in patients with a serum potassium concentration of ≥4.5 mEq/L. Studies investigating consequences of hypokalemia after acute myocardial infarction revealed conflicting results. Therefore, the aim of this systematic review and meta-analysis was to combine evidence from previous studies on the association of serum potassium concentration with both short and long-term mortality as well as the occurrence of ventricular arrhythmias. Design: Systematic review and meta-analysis. Methods: A structured search of MEDLINE and EMBASE databases yielded 23 articles published between 1990 and January 2017 that met the inclusion criteria. Study selection, data extraction and quality assessment were carried out by three reviewers. Random effects models were used to pool estimates across the included studies and sensitivity analyses were performed when possible. Results: Twelve studies were included in the meta-analysis. Both pooled results from six studies investigating short-term mortality and from five studies examining long-term mortality revealed significantly increased risks in patients with serum potassium concentrations of <3.5 mEq/L, 4.5–<5.0 mEq/L and ≥5.0 mEq/L after acute myocardial infarction. In addition, a serum potassium concentration of <3.5 mEq/L was significantly associated with the occurrence of ventricular arrhythmias. Conclusions: Mortality, both short and long term, and the occurrence of ventricular arrhythmias in patients with acute myocardial infarction seem to be negatively associated with hypokalemic serum potassium concentration. There is evidence for adverse consequences of serum potassium concentrations of ≥4.5 mEq/L. Due to the heterogeneity among existing studies, further research is necessary to confirm the need to change clinical practice guidelines.